2018
DOI: 10.3390/ijms19020643
|View full text |Cite
|
Sign up to set email alerts
|

Fine Physical Bin Mapping of the Powdery Mildew Resistance Gene Pm21 Based on Chromosomal Structural Variations in Wheat

Abstract: Pm21, derived from wheat wild relative Dasypyrum villosum, is one of the most effective powdery mildew resistance genes and has been widely applied in wheat breeding in China. Mapping and cloning Pm21 are of importance for understanding its resistance mechanism. In the present study, physical mapping was performed using different genetic stocks involving in structural variations of chromosome 6VS carrying Pm21. The data showed that 6VS could be divided into eight distinguishable chromosomal bins, and Pm21 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…speltoides Pm12 (6SS) and D. villosum Pm21 (6VS) are both located on the short arms of the homoeologous group 6 chromosomes. To evaluate the collinearity relationship, we used a set of Pm21- associated 6VS markers reported previously ( He et al., 2016 ; Zhu et al., 2018 ) to detect the Pm12 and Pm21 regions. The results revealed that 9 of 46 6VS markers showed polymorphisms between Pm12 -carrying materials (WL31 and 1338-8) and Pm12 -null common wheat YM9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…speltoides Pm12 (6SS) and D. villosum Pm21 (6VS) are both located on the short arms of the homoeologous group 6 chromosomes. To evaluate the collinearity relationship, we used a set of Pm21- associated 6VS markers reported previously ( He et al., 2016 ; Zhu et al., 2018 ) to detect the Pm12 and Pm21 regions. The results revealed that 9 of 46 6VS markers showed polymorphisms between Pm12 -carrying materials (WL31 and 1338-8) and Pm12 -null common wheat YM9.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to genetic analysis, chromosomal deletion analysis is also an efficient method for finely mapping a gene of interest ( Zhu et al., 2018 ). Here, using chromosome deletion lines induced by irradiation that are susceptible to powdery mildew, we quickly revealed that the Pm12 locus corresponds to the Pm21 orthologous region of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…SCVs involve rearrangements of large DNA sequences; the genetic effects of natural SCVs in Arabidopsis (Fransz et al., 2016) and Brassica napus (Stein et al., 2017) have been determined. In wheat, many natural SCVs have been reported (Badaeva et al., 2007; Huang et al., 2018; Walkowiak et al., 2020; Wu et al., 2021), and the genetic effects of several wheat–alien translocations have been readily identified and used in breeding (Crespo‐Herrera et al., 2017; Zhu et al., 2018). However, little is known about intra‐wheat translocations and larger PAVs.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that frequent SCVs have occurred in wheat evolution and cultivar development. Moreover, alien introgression has played important roles in modern wheat breeding, mainly because wheat–alien translocations have had positive effects in wheat improvement efforts (Crespo‐Herrera et al., 2017; Subbarao et al., 2021; Wang, Sun, et al., 2020; Zhu et al., 2018). China has been recognized as a secondary wheat diversity center, with rich genetic variation (Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been extensively used as a vital genetic resource for wheat breeding. Since the last century, several D. villosum –common wheat alien lines, such as amphidiploids [ 19 ], additional lines [ 20 ], substitution lines [ 21 , 46 ] and translocation lines [ 47 , 48 , 49 ], have been developed, and several resistance genes, such as Pm62 [ 18 ], Pm21 [ 50 ] , Sr52 [ 51 ], have been explored and mapped on individual V-genome chromosomes by using wheat– D. villosum alien lines. In 2000, Yildirim et al [ 17 ] tested the stripe rust reactions of D. villosum accessions, and the results showed that, of the 115 D. villosum accessions tested, 41 (35.65%) were resistant to stripe rust, indicating that D. villosum provides a vast pool of genes for stripe rust resistance.…”
Section: Discussionmentioning
confidence: 99%